STAFFING CHALLENGES IN HEALTH CARE (SOCIAL AND ECONOMIC ASPECTS) - K. A. Egiazaryan; L. Zh. Attayeva (Медицинский вестник Юга России, 2013)
In any branch of modern economy the most important factor of production is work. In the last decades work specializes in the health care sphere more and more. The role of laboratory assistants, technicians, technologists, engineers, economists, managers and financiers considerably increases in medical institutions. Features of work in health care are connected with specifics of made «product». So, despite rapid development of new technologies in medicine, replacement of work with the capital here is possible only in limited limits. It is a classical example of branch where work, i.e. «the human capital» and the capital material act rather as complements, than substitutes. For this reason the most important strategic component of development of health care is optimization of management by personnel resources.